Economic Regulation of Urban Water and Sanitation Services : Some Practical Lessons - Ehrhardt, David; Groom, Eric; Halpern, Jonathan; O'Connor, Seini (World Bank, Washington, DC, 2014)
This paper discusses the regulation of water and sanitation services in urban areas. Specifically, it explores ways of thinking about regulatory design as part of a wider, country-specific program to reform the way in which water supply and sanitation services are provided and paid for. In the past, regulatory advisers often focused on the need to introduce international best practice- generally in the form of an independent regulatory organization-to solve a wide range of performance problems. However, this approach was seldom straightforward, nor was it always successful. There is no one-size-fits-all regulatory design that can be reliably applied to resolve performance problems. Rather, regulation is best developed on a country-by-country basis through answering questions such as the following: a) What are the real sector problems, and which of these can regulation solve? b) What specific objectives is regulation aiming to achieve? c) What combination of organizations and instruments is most suitable and would work best for achieving these regulatory objectives? This paper is not intended to be a detailed guide for regulatory design. Rather, it discusses how to approach regulatory design. This approach encourages decision makers and their advisors to apply sound principles within country-specific settings, rather than advocate best-practice models without a thorough analysis of whether these are suitable for the country's context. The best combination of rules and institutions for setting tariffs and service standards3,-and indeed, the best reform options in general-will vary from country to country. Regulatory designers should select this combination by first focusing on the principal sector objectives and working with institutions that may already be responsible for achieving them.